The Influence of Food Quality And Dinescape on Customer Satisfaction in Restaurants in Garut District West Java Province - Gugung Gumilar; Siska Mandalia (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
The background of the study was coming from the restaurant customer complaints in Garut to the food quality amounting to 21.58% and to the restaurant dinescapes amounting to 20.86%, each of which caused a decrease in the number of customers. This complaint data was found since the researcher has participated in the organization of AKAR (Association of Café and Restaurant) for Garut area. The decrease of customers’ visit showed that the quality and the dinescape of the restaurants in Garut are not satisfying. This research is aimed at identifying the food quality, analyzing the restaurant dinescape, and knowing to what extent the influence of food quality toward the restaurants dinescapes in Garut. The research method in this study was the survey explanatory whose characteristic is descriptive and verificative. Data were gathered through questionnaire distributed to respondents; they are the restaurant customers in Garut. The number of questionnaires spread out were 381 respondents and responded by Cargo, D’Anclom and Lify Eatery restaurants di Garut. The data was analysed using Path Analysis which is assisted by SPSS 21.0 system. The result of analysis shows that the food quality and dinescape of Cargo, D’Anclom, and Lify Eatery restaurants are not good. In addition, the data analysis also indicates that the food quality and dinescape of the restaurant influence significantly the customers’ satisfaction in Garut with the total of influence amounting to 85.3%. Based on the result of study, it could be identified that the food quality and dinescape must be of great importance to be paid much attention by the owners because the food quality and dinescape which are served well are potential to the restaurant managements to be able to keep the customers as one of high profitable sources for restaurants.